POSITIVE DISCIPLINE: SOLUTION TO BOOST STUDENTS’ SELF ESTEEM IN LEARNING ENGLISH AS FOREIGN LANGUAGE - Nur Muthmainnah (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
This theoretical concept is aimed to investigate how positive discipline is implemented in foreign language classroom and improve students’ self-esteem. As one of forms of classroom management, positive discipline expects long-term discipline planted in the learners’ behavior. There are five principles of positive discipline which can be implemented in language learning; Identifying long-term goals; Providing warmth and structure; Understanding child development; Identifying individual differences; Problem-solving and responding with positive discipline. The implementation of positive discipline which support classroom encouragement and confidence could improve learner’s self-esteem. By implementing the positive discipline, teacher also takes advantages on understanding more about his students’ character. In addition, learner would realize their long-term goal of learning foreign language which motivates them to be more active in the class.